2012
DOI: 10.23986/afsci.6387
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality response of broccoli florets to combined application of 1-methylcyclopropene and modified atmosphere packaging

Abstract: Broccoli is rich in health-promoting compounds such as ascorbic acid and glucosinolates. However, amount of such compounds inevitably decrease along with the storage. This study was conducted to investigate the effects of 1-methylcyclopropene (1-MCP) and Modified Atmosphere Packaging (MAP) treatments alone or in combination on postharvest life and quality of broccoli heads during cold storage. MAP and 1-MCP+MAP significantly reduced weight loss, delayed surface color changes and chlorophyll breakdown, maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
8
0
3
Order By: Relevance
“…High temperatures and low relative humidity can slow down the activities of superoxide dismutase, catalase and peroxidase, eventually lowering the oxygen radical production that leads to the yellowing of broccoli (Singh andDwivedi, 2008: Yuan 2010). Whilst temperature and humidity control are likely to be the main methods to delay yellowing, some studies have shown that post-harvest treatment with 1-MCP can also reduce the pace of yellowing in broccoli florets at 20°C (Yuan et al, 2010: Sabir, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures and low relative humidity can slow down the activities of superoxide dismutase, catalase and peroxidase, eventually lowering the oxygen radical production that leads to the yellowing of broccoli (Singh andDwivedi, 2008: Yuan 2010). Whilst temperature and humidity control are likely to be the main methods to delay yellowing, some studies have shown that post-harvest treatment with 1-MCP can also reduce the pace of yellowing in broccoli florets at 20°C (Yuan et al, 2010: Sabir, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Total chlorophyll and total anthocyanin contents slightly decreased at 4°C because thyme oil application prevented the degradation of anthocyanin and chlorophyll (Figures 6 and 7), but this might be lost at the control, which may be associated with water loss (Haminiuk et al 2012;Sabir 2012). Thyme oil increased glucosinolates content in 3-day-old sprouts, compared to control treatments (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Green broccoli ( Brassica oleracea L.) is an edible vegetable with high nutritional value (Khalili et al ., ). It has been reported to be rich in antioxidants (Mollica et al ., ), health promoting phytochemicals as glucosinolates (Hanschen et al ., ), anti‐carcinogenic compounds (Kiani et al ., ) or vitamins (Sabir, ). According to 2016 data, the world production of cauliflower and broccoli is around 25 million tonnes per year, corresponding to the European production about 10% (FAOSTAT, ).…”
Section: Introductionmentioning
confidence: 99%